The cost-effectiveness of tumor-treating fields therapy in patients with newly diagnosed glioblastoma. Issue 8 (13th May 2016) - Bernard-Arnoux, F.; Lamure, M.; Ducray, F.; Aulagner, G.; Honnorat, J.; Armoiry, X.
Abstract: Background: There is strong concern about the costs associated with adding tumor-treating fields (TTF) therapy to standard first-line treatment for glioblastoma (GBM). Hence, we aimed to determine the cost-effectiveness of TTF therapy for the treatment of newly diagnosed patients with GBM. Methods: We developed a 3-health-state Markov model. The perspective was that of the French Health Insurance, and the horizon was lifetime. We calculated the transition probabilities from the survival parameters reported in the EF-14 trial. The main outcome measure was incremental effectiveness expressed as life-years gained (LYG). Input costs were derived from the literature. We calculated the incremental cost-effectiveness ratio (ICER) expressed as cost/LYG. We used 1-way deterministic and probabilistic sensitivity analysis to evaluate the model uncertainty. Results: In the base-case analysis, adding TTF therapy to standard of care resulted in increases of life expectancy of 4.08 months (0.34 LYG) and €185 476 per patient. The ICER was €549 909/LYG. The discounted ICER was €596 411/LYG. Parameters with the most influence on ICER were the cost of TTF therapy, followed equally by overall survival and progression-free survival in both arms. The probabilistic sensitivity analysis showed a 95% confidence interval of the ICER of €447 017/LYG to €745 805/LYG with 0% chance to be cost-effective at a threshold of €100 000/LYG. Conclusion: The ICER of TTF therapy at first-line treatment is far beyond conventional thresholds due to the prohibitive announced cost of the device. Strong price regulation by health authorities could make this technology more affordable and consequently accessible to patients.